Análise de projetos de melhoria da produção: concepção de ferramenta estruturada e estudos de caso - Lizarelli, Fabiane Letícia (Universidade Federal de São Carlos, 2008)
The capacity to improve the processes has been considered as an important factor for the companies competitiveness. However, the improvement activities don't happen spontaneously, people involved must have knowledge and abilities, besides domain on techniques and methods to achieve the improvement. Therefore, the company needs to invest in training, to make possible that the people involved in improvement projects dedicate time, and to support with financial and organizational resources. This investment will be applied to accomplish improvement projects, but, however, how to verify if the efforts are being used in an effective way? For that, it is necessary to measure the efforts allocated for the accomplishment of the activities and to compare with the obtained results. The importance of this study is its contribution for the evaluation of improvement projects. Besides, the theme has relevance, considering the shortage of works that analyze the factors involved for the accomplishment of improvement actions, quantify them and compare with the obtained results. The bases for that investigation are the descriptions found in the literature, they present the efforts involved for the improvement accomplishment and the possible results. For the investigation, some approaches were analyzed, like Total Quality Management, Kaizen and Six Sigma, identifying the efforts that each one judges necessary for the improvement and to achieve results. All these information helped to create a structured tool to measure and to characterize the improvement projects. To use the tool are necessary some procedures, of rising and analysis data related to the projects efforts and results. This work was developed using multiple cases study, were investigated four companies, which have improvement culture disseminated, guaranteed by the use of programs like Lean Production and Six Sigma, allowing an analysis of different improvement project types. It was verified that utilizing the tool developed in this research was possible to evaluate the improvement projects, verifying the relation between efforts and results.
Keywords: Melhoria contínua; Produção enxuta; Seis sigma; Gestão de projetos; Melhoria da produção; Projetos de melhoria; Production improvement; Continuous improvement; Lean production; Six sigma; Improvement projects; ENGENHARIAS::ENGENHARIA DE PRODUCAO